A Review on Blockchain Operations in Construction Management - Hasan Volkan Oral; Bassant Sayed (Journal of Sustainable Construction Materials and Technologies, 2023)
This study investigates the important role that the blockchain plays to manage the information about who did what and when and hence provides a strong base for any legal potential conflicts. Blockchain technology permits you to distribute, encrypt, and secure the records of digital transactions. In addition, bitcoin and other cryptocurrencies are encompassed in it. Even though the construction industry has traditionally been a late user of innovative technology compared to other sectors of the economy, it faces various hurdles in terms of trust, accessibility, information sharing, and process automation. As a result, stakeholders, clients, subcontractors, contractors, and suppliers have been unable to work together effectively. Even if building information modeling is employed, which envisions a centralized building, the primary benefit of blockchain is the secure storage of sensitive sensor data.